Experimental investigation of miniature energy harvester driven by air flow - Ng, Chai Chi (2016)
Wind turbine is an oscillatory motion where power is produced based on the conversion of the kinetic energy from the wind. It is caused by the motion of the wind where the air is forced to move in one direction while the blade is pushed in the other, resulting the rotor to start to turn. However, such self-sustained rotation, may be converted to electrical energy using an AC motor. In this project, the self-sustained rotation is analyzed on 2 different number of blades with each having 3 different sizes. Energy harvesting is achieved by using a AC motor that is located at the end of the shaft. There are a total of 6 different configurations that are used in the implementation of the oscilloscope and their respective voltages are measured. It was found that the propeller with the highest number of blades and largest in diameter size generated the highest RPM (revolution per minute) as compared to the other propeller sizes. It was also discovered that the larger the radius of the propeller, more energy can be generated and efficiency increases.